No evidence of tocilizumab treatment efficacy for severe to critical SARS-CoV2 infected patients: Results from a retrospective controlled multicenter study. Issue 21 (28th May 2021) - Burlacu, Ruxandra; London, Jonathan; Fleury, Audrey; Sené, Thomas; Diallo, Abdourahmane; Meyssonnier, Vanina; Zeller, Valérie; Galland, Joris; Huscenot, Tessa; Rubenstein, Emma; Trouiller, Pierre; Amathieu, Roland; et al.
Abstract : Abstract: To assess tocilizumab (TCZ) efficacy associated to standard of care (SOC) compared to SOC alone in severe coronavirus associated disease 2019 (COVID-19) patients. In a matched case-control study from 3 French Hospital COVID-19 Departments, 27 patients with severe COVID-19 treated with TCZ and SOC were matched for baseline epidemiological and clinical features and compared to 27 severe COVID-19 patients treated with SOC alone. Baseline characteristics of the study population were comparable between groups. Eleven patients (20%) died. TCZ was not associated with clinical improvement as compared to SOC regarding oxygen-free status (44% vs 63%) and death (18.5% vs 22%), despite a higher decrease of the C-reactive protein at Day 7 (10.7 vs 52 mg/L; P  < 10 −3 ). Compared to the 43 patients alive at the end-of follow-up, patients who died were older (78 vs 64 years; P  < 10 −3 ), with 82% of them older than 72 years vs only 23% of live patients ( P  < 10 −3 ). Age (OR = 1.15; 95%CI = 1.04–1.3; P  = .008) and age over 72 years (OR) = 14.85; 95%CI = 2.7–80; P  = .002) were independently associated with mortality. TCZ in addition to SOC for severe COVID-19 patients did not reduce mortality, subsequent need for invasive mechanical ventilation nor did it shorten the time of oxygen support, despite better control of the inflammatory response. More powerful and randomized controlled trials are warranted to determine if TCZ is effective in the management of COVID-19.